Explaining External Competitiveness and Trade Capacity in Developing Economies: A Panel Data Analysis - Pulaj, Ilira; Guga, Klaudja; Serjanaj, Lorena (Theoretical and Practical Research in Economic Fields; Vol 17 No 2 (2026): TPREF Volume XVII Issue 2(38) June 2026, 2026)
mpetitiveness and trade capacity are critical determinants of sustainable growth in developing economies, particularly in an increasingly globalized and knowledge-based economic environment. While trade openness expands access to international markets, long-term competitiveness depends on a country’s ability to innovate, share knowledge, and adopt new technologies. This study empirically examines the relationship between innovation-related factors and external competitiveness, using high-technology exports as a proxy for trade capacity and competitive performance. The analysis is based on panel data from 33 developing countries over the period 2010–2021 and employs a fixed-effects regression model to assess the association between university–industry collaboration, research and development (R&D) intensity, human capital, and information and communication technology (ICT) adoption, and high-tech export performance. The findings indicate that innovation systems are closely associated with external competitiveness. University–industry collaboration shows the strongest and most robust positive association with competitiveness, followed by R&D intensity and ICT adoption. In contrast, human capital does not exhibit a statistically significant direct association, suggesting that its contribution to trade capacity may operate indirectly through innovation processes and absorptive capacity. Overall, the results highlight the importance of integrated innovation systems and institutional coordination in supporting technological export performance and facilitating participation in global trade networks. Policies supporting innovation, digitalization, and university–industry collaboration are closely associated with improvements in technological capabilities and broader socio-economic development.